Pharmacognostical and Pharmaceutical Evaluation of Vasa Avaleha An Ayurvedic Compound - A Chaudhary, Vd Suhas (International Journal of Pharmaceutical & Biological Archive, 2015)
Pharmacognostical and Pharmaceutical Evaluation of Vasa Avaleha An Ayurvedic Compound